Ecogenomics-Based Mass Balance Model Reveals the Effects of Fermentation Conditions on Microbial Activity - Kim, Jinha; Mei, Ran; Wilson, Fernanda P.; Yuan, Heyang; Bocher, Benjamin T. W.; Liu, Wen-Tso (Frontiers in Microbiology, 2020)
Fermentation of waste activated sludge (WAS) is an alternative approach to reduce solid wastes while providing valuable soluble products such as volatile fatty acids and alcohols. This study systematically identified optimal fermentation conditions and key microbial populations by conducting two sets of experiments under different combinations of biochemical and physical parameters. Based on fermentation product concentrations, methane production, and solid removal, fermentation performance was enhanced under the combined treatments of inoculum heat shock (>60°C), pH 5, 55°C, and short solid retention time (<10 days). An ecogenomics-based mass balance (EGMB) approach was used to determine the net growth rates of individual microbial populations, and classified them into four microbial groups: known syntrophs, known methanogens, fermenters, and WAS-associated populations. Their growth rates were observed to be affected by the treatment conditions. The growth rates of syntrophs and fermenters such as Syntrophomonas and Parabacteroides increased with a decrease in SRT. In contrast, treatment conditions such as inoculum heat shock and high incubation temperature inhibited the growth of WAS-associated populations such as Terrimonas and Bryobacter. There were also populations insensitive to the treatment conditions such as those related to Microbacter and Rikenellaceae. Overall, the EGMB approach clearly revealed the ecological roles of important microbial guilds in the WAS fermentation system, and guided the selection of optimal conditions for WAS fermentation in future pilot-scale operation.